2021
DOI: 10.1177/14759217211018114
|View full text |Cite
|
Sign up to set email alerts
|

A two-step method for delamination detection in composite laminates using experience-based learning algorithm

Abstract: Delamination in composite laminates reduces the structural stiffness and thus causes changes in the vibration responses of the laminates. Therefore, it is feasible to employ dynamic characteristics (such as natural frequencies and mode shapes) for delamination detection by using an optimization method. In the present study, a two-step method is proposed for the delamination detection in composite laminates using an experience-based learning algorithm. In the first step, one-dimensional equivalent through-thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…14,15 In recent years, there has been an increasing trend among scholars to utilize vibration-based methods for damage identification. 16,17 It is widely recognized that structural damage affects the mass, stiffness, and damping properties of a structure, consequently altering its vibrational response. 18,19 Based on the extracted damage identification features, the dynamic parameters are classified into four categories: natural frequency-based methods, mode shape-based methods, curvature/strain mode shapebased methods, and methods based on the combination of mode shape and frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 In recent years, there has been an increasing trend among scholars to utilize vibration-based methods for damage identification. 16,17 It is widely recognized that structural damage affects the mass, stiffness, and damping properties of a structure, consequently altering its vibrational response. 18,19 Based on the extracted damage identification features, the dynamic parameters are classified into four categories: natural frequency-based methods, mode shape-based methods, curvature/strain mode shapebased methods, and methods based on the combination of mode shape and frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic characteristics of composite tube components play a crucial role in the analysis of their dynamic responses and are of great importance in vibration control 14,15 . In recent years, there has been an increasing trend among scholars to utilize vibration‐based methods for damage identification 16,17 . It is widely recognized that structural damage affects the mass, stiffness, and damping properties of a structure, consequently altering its vibrational response 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Damage detection algorithm developed by Sahin and Shenoi 14 was combined with local (curvature MSs) and global (changes in natural frequencies) vibrationbased analysis data as supplied to artificial neural network to assess the severity and location of damage in beam structure. Zheng, et al 15 conducted an optimization method for detection of different delamination situations in laminated composite structures by using experimental and numerical study. They stated that the dynamic characteristics (MSs and natural frequencies) can be used for delamination detection by applying an experience-based learning algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Their analysis results indicated that the proposed method is in good agreement with the Hashin model. Zheng et al [30] proposed a twostep technique experience-based learning algorithm to identify delamination in composite beams. They used one-dimensional equivalent through-thickness beam elements to model the composite beam and to identify the potential delamination locations.…”
Section: Introductionmentioning
confidence: 99%